Creative visualisation in chemistry. (2016) - Bowen, Jonathan P.; Bowen, Alice M.; Harrison, Karl
Visualisation of molecules in the field of chemistry has been important for understanding their structure, whether simple or complicated. Initially, this was done by hand, but latterly software has come to the aid of researchers and the vast majority of chemistry visualisation is now computer-generated. As well as aiding understanding, many molecules, especially if complex in nature, can take on an artistic quality when visualised, using artificial colour for example. Often these are used for creative reasons on the front of chemistry journals, for example, and sometimes as an inspiration for more pure art forms. This paper introduces molecular graphics in the context of creative computing. It also provides a history of the development of visualisation in chemistry, especially more recently with the use of software and the increasing use on journal covers. A brief survey of some of the software involved is included. Finally, some conclusions are drawn with respect to the creative directions being taken now and possible directions in the future.